2014
DOI: 10.1002/2013jd020513
|View full text |Cite
|
Sign up to set email alerts
|

Northern PMC brightness zonal variability and its correlation with temperature and water vapor

Abstract: Analyses of all days of the five northern seasons from 2007 to 2011 indicate that temperature and albedo daily zonal variations are anticorrelated in the season start and end, whereas in the core of the season the correlation is relatively poor. The albedo and H 2 O correlation in the zonal direction is poor throughout the season. Zero-dimensional model physics indicates that when clouds are weaker, or the environment is warmer and drier, temperature plays an increasingly important role in determining the clou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 36 publications
1
11
0
Order By: Relevance
“…They furthermore showed that this IWC is in agreement with zonally averaged IWC observed by SOFIE to within 35%, indicating that vertical and horizontal transport of PMC can be neglected when calculating IWC at SOFIE latitudes. The model has been successfully used in a variety of PMC studies at high latitudes and midlatitudes [ Russell et al ., , ; Rong et al ., , ; Hervig et al ., , ]. We will discuss our assumption of local PMC formation when comparing our PMC calculations against observations later in this study.…”
Section: Nogaps‐alpha and Pmcmentioning
confidence: 99%
“…They furthermore showed that this IWC is in agreement with zonally averaged IWC observed by SOFIE to within 35%, indicating that vertical and horizontal transport of PMC can be neglected when calculating IWC at SOFIE latitudes. The model has been successfully used in a variety of PMC studies at high latitudes and midlatitudes [ Russell et al ., , ; Rong et al ., , ; Hervig et al ., , ]. We will discuss our assumption of local PMC formation when comparing our PMC calculations against observations later in this study.…”
Section: Nogaps‐alpha and Pmcmentioning
confidence: 99%
“…Hervig et al (2009) also concluded that the PMC seasonal dependence is generally controlled by temperature. Rong et al (2014) found that during the summer season start and end, the temperature plays a dominant role in influencing the PMC variability.…”
Section: Introductionmentioning
confidence: 95%
“…Water vapor is another important factor for the PMC formation. However, using Aeronomy of Ice in the Mesosphere (AIM) and Aura/MLS satellite data between 2007 and 2011, Rong et al (2014) found that the correlation of albedo and H 2 O (without time lag) is poor throughout the season in the NH, while temperature and albedo are clearly anticorrelated during the season start and end. Therefore, we will only study the correlation between temperature and PMCs during the PMC startup season in this paper.…”
mentioning
confidence: 99%
“…[] and similar to Rong et al . [, ] and Russell et al . [], the MLS temperature and H 2 O data at the pressure layer of 0.0046 hPa (~84 km) are used to represent the temperature and H 2 O at the PMC layer.…”
Section: Data Setsmentioning
confidence: 99%